Religious Authority and Economic Boycott: Critical Analysis of MUI Fatwa No. 83/2023 in the Framework of Economic Warfare: Otoritas Keagamaan dan Boikot Ekonomi: Analisis Kritis Fatwa MUI No. 83/2023 dalam Kerangka Perang Ekonomi - Sumar'in; Andi Maryam (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2025)
Although various studies have examined the economic and political impacts of product boycotts, research focusing on the implementation of economic boycotts driven by religious fatwas in the Indonesian context remains scarce. This study seeks to fill that gap by analyzing the Indonesian Ulema Council (Majelis Ulama Indonesia) Fatwa No. 83/2023 concerning support for the Palestinian cause and the boycott of pro-Israel products, within the framework of fiqh siyasah and the concept of economic warfare. Using a descriptive qualitative method with a contextual content analysis approach, this research explores the substance and implications of the fatwa. The analysis finds that the fatwa emphasizes the moral and political dimensions of Muslim solidarity, positioning boycotts and the distribution of zakat and infaq as forms of ethical and humanitarian responsibility rather than economic instruments. Furthermore, the fatwa illustrates the integration of fiqh siyasah principles into contemporary discourse on global justice and Muslim solidarity. This study contributes to a deeper understanding of how religious authority can influence moral reasoning and collective action within Islamic economic thought. The findings provide conceptual insights for scholars, policymakers, and community leaders on the role of Islamic legal perspectives in shaping ethical responses to global political issues, while promoting peaceful and principled engagement in international relations.